Engaging in Physical Activity in Green Spaces at Night Is Associated with Mental Well-Being and Happiness - Chun Jiang; Xing Zhang; Siyuan Feng; Hansen Li (Behavioral Sciences)
This study aims to explore the impact of the timing (day vs. night) and location (green space vs. non-green space) of outdoor physical activity on college students’ mental health. We designed a cross-sectional study based on self-reported data, asking participants to recall their physical activity and mental health status over the past month through a questionnaire. Specifically, a survey was conducted at a university in Chongqing, collecting data on outdoor physical activity and mental health indicators (including anxiety, depression, mental well-being, life satisfaction, happiness, and stress) from 418 students (75 females). The questionnaire was distributed via an online platform, allowing students to complete it using either their mobile phones or computers. The data collection took place in December 2024. The results showed that about half of the participants preferred engaging in outdoor physical activity in the nighttime, with most choosing green spaces. Regression analysis revealed that participants who engaged in outdoor physical activity at night had significantly lower anxiety levels compared to those who engaged in outdoor physical activity during the day (mean difference (MD) = −1.015; 95% CI = −1.974 to −0.055; p = 0.038). Additionally, compared to participants who engaged in outdoor physical activity in green spaces, those who engaged in physical activity in non-green spaces reported lower levels of mental well-being (MD = −1.531; 95% CI = −2.480 to −0.582; p = 0.002) and subjective happiness (MD = −0.462; 95% CI = −0.917 to −0.007; p = 0.047). Sensitivity analysis indicated that, for those who participated in nighttime activities, engaging in outdoor physical activity in green spaces was associated with higher levels of mental well-being (MD = 2.025; 95% CI = 0.810 to 0.324; p = 0.001) and happiness (MD = 0.583; 95% CI = 0.026 to 1.140; p = 0.040). Sensitivity analysis also revealed slight gender differences; however, the findings related to females should be interpreted with caution due to the insufficient sample size. Overall, despite some differences in time and location choices, engaging in outdoor physical activity at night in green spaces appears to associate with college students’ health, particularly their happiness and mental well-being. This study provides preliminary evidence of the potential benefits of nighttime green outdoor physical activity for improving college students’ mental health and offers directions for future research in this area.